2004
DOI: 10.1074/jbc.m311203200
|View full text |Cite
|
Sign up to set email alerts
|

Mutant (R406W) Human Tau Is Hyperphosphorylated and Does Not Efficiently Bind Microtubules in a Neuronal Cortical Cell Model

Abstract: Frontotemporal dementia and Parkinsonism linked to chromosome 17 (FTDP-17) is an autosomal dominant neurodegenerative disorder caused by mutations in the gene that encodes for tau, a microtubule-binding protein. Neuropathologically the disease is characterized by extensive neuronal loss in the frontal and temporal lobes and the filamentous accumulation of hyperphosphorylated tau. The R406W missense mutation was originally described in an American and a Dutch family. Although R406W tau is hyperphosphorylated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 63 publications
3
31
0
Order By: Relevance
“…In cell lines, 4L R406W seems not to be phosphorylated at Ser-396, although another study found it to be phosphorylated to a similar extent as the wild-type tau (49). Consistent with the present study, when 4L R406W was expressed in a neuronal cortical cell model (52), it was found to be phosphorylated at several sites, including Ser-396, and unable to bind to microtubules due to the phosphorylation state. In 4L R406W transgenic mice, the protein was found to be phosphorylated at several sites, including Ser-396, and to be aggregated into filaments (53).…”
Section: Discussionsupporting
confidence: 78%
“…In cell lines, 4L R406W seems not to be phosphorylated at Ser-396, although another study found it to be phosphorylated to a similar extent as the wild-type tau (49). Consistent with the present study, when 4L R406W was expressed in a neuronal cortical cell model (52), it was found to be phosphorylated at several sites, including Ser-396, and unable to bind to microtubules due to the phosphorylation state. In 4L R406W transgenic mice, the protein was found to be phosphorylated at several sites, including Ser-396, and to be aggregated into filaments (53).…”
Section: Discussionsupporting
confidence: 78%
“…While there is no evidence of neuronal apoptosis in mouse models of tauopathy, in the Drosophila model, neuronal cell death is consistent with an apoptotic mechanism (28,34). Moreover, the tau mutations R406W, V337M, and N279K, associated with frontotemporal dementia, were shown to enhance the vulnerability of cultured neurons to apoptotic stressors (51,52). Interestingly, hallmarks of both apoptotic and necrotic cell death have been recently identified in neurons from transgenic mice expressing nonmutant forms of human tau (53).…”
Section: Figurementioning
confidence: 99%
“…When expressed in SH-SY5Y cells subsequently differentiated into neurons, the R406W, P301L, and V337M mutations reduce tau phosphorylation (23). In contrast, in hippocampal neurons, R406W increases tau phosphorylation (24). When phosphorylated by recombinant GSK3␤ in vitro, the P301L and V337M mutations do not have any effect, and the R406W mutation inhibits phosphorylation (25).…”
mentioning
confidence: 94%